PENGARUH BERMAIN THROW AND CACTH THE BALL TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK DI KB SEROJA, OGAN KOMERING ULU - Kurniawati, Annisa; Handayani, Tutut; Handayani, Muhtarom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Throw and Catch The Ball activity on the gross motor development of Group B children at KB Seroja, Ogan Komering Ulu. This research was motivated by the problem of gross motor development that had not yet developed optimally, particularly in the coordination of hand and eye movements during ball throwing and catching activities. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 22 children aged 5–6 years who were selected using a purposive sampling technique. Data collection techniques included observation, tests, and documentation using a gross motor development observation sheet covering hand-eye coordination, balance, agility, arm muscle strength, accuracy, endurance, and cooperation. Data analysis was conducted using SPSS through normality testing, homogeneity testing, and hypothesis testing (Paired Sample T-test). The results of the study indicate that there was a significant improvement in children’s gross motor development after being given treatment in the form of Throw and Catch The Ball activities. The mean pretest score of 22.45 increased to 30.00 in the posttest, with an improvement difference of 7.55. The posttest frequency distribution showed that 100% of the children achieved the maximum score, indicating that their gross motor development improved optimally. The results of the Paired Sample T-test showed a significance value of 0.00 < 0.05, thus it can be concluded that the Throw and Catch The Ball activity has a significant effect on the gross motor development of Group B children at KB Seroja, Ogan Komering Ulu. Therefore, the Throw and Catch The Ball activity is effective as a fun and innovative learning method that can optimally and comprehensively improve early childhood gross motor skills.